Development of Breast Self-Examination (BSE) Instrument on Midwifery Student - lestari, sri; Rusilowati, Ani; Kasmini Handayani, Oktia Woro (Journal of Research and Educational Research Evaluation, 2018)
Breast self-examination (BSE) is one of the steps taken to measure the level of validity and reliability. The purpose of this research is to develop a valid, reliable and practical BSE assessment instrument. Small-scale test data was obtained at Muhammadiyah University Semarang (UNIMUS) with 50 students, data field test data was obtained at Kudus Academy and Stikes Widya Husada Semarang with 110 students. Data analysis using source triangulation, grain validity, explanatory factor analysis (EFA), Alpha Cronbach reliability and two way anava and re-analyzed using Hoyt formula and practicality test. The research method used is research and development (R & D). The result of validity of small grains of 26 grains is valid, for anti-image correlation of 26 grains and 3 grains is not valid, small scale reliability value 0.714 and KMO result in field trial show value equal to 0,945, MSA> 0,5 and significance of Barlett test equal to 0,000. The assessment instrument developed is valid constructively because it is able to explain the overall variation of the BSE materials. The reliability value of alpha cronbach is 0.970. Practical results show the BSE instrument in the "very practical" category"The benefits of this study can be a reference in the steps of development of instruments that can support the quality of teaching and learning process of midwifery students.